Infinite powers : how calculus reveals the secrets of the universe - Strogatz, Steven (Boston, Massachusetts : Houghton Mifflin Company, 2019)
Steven Strogat'z brilliantly creative, down-to-earth history shows that calculus is not about complexity; it's about simplicity. It harnesses an unreal number--infinity--to tackle real-world problems, breaking them down into easier ones and then reassembling the answers into solutions that feel miraculous. Starting with calculus's origins in ancient Greece, Infinite Powers reveals how this form of math rose to the challenges of each age, from determining the area of a circle to making electricity with magnets to turning the tide in the fight against AIDS to spearheading the discovery of gravitational waves. As Strogatz proves, calculus is truly the language of the universe. By unveiling the principles of that language, Infinite Powers makes us marvel at the world anew
Introduction -- 1. Infinity -- 2. The Man Who Harnessed Infinity -- 3. Discovering the Laws of Motion -- 4. The Dawn of Differential Calculus -- 5. The Crossroads -- 6. The Vocabulary of change -- 7. The Secret Fountain -- 8. Fictions of the Mind -- 9. The Logical Universe -- 10. Making Waves -- 11. The Future of Calculus.
Includes bibliographical references and index.
Keywords: CALCULUS